FUNKSIYA TUSHUNCHASI. LOGARIFMIK FUNKSIYA VA UNING FORMULALARI - Siddiqov Bahodir Bahromjon o`g`li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article deals with the most common term in mathematics - function. Also, the graphic representation of the function in the coordinate system is explained in the case of a linear function.